Two-year performance study of porous, thermoset, shape memory polyurethanes intended for vascular medical devices. (21st February 2017) - Weems, Andrew C; Boyle, Anthony J; Maitland, Duncan J
Abstract: The long-term shape-recovery behavior of shape memory polymers has often been shown to be dependent on the length of time the material has been stored in the secondary shape. Typically, recovery performance and shape fixity will decrease with increased time in the secondary shape. In medical materials, a shelf-life is crucial to establish as it sets the upper threshold for device performance in a clinical setting, and a reduction in shape recovery would limit the development of SMP medical devices. Here, we present a two-year study of strain recovery, strain fixity, and shape recovery kinetics for passively and actively actuated SMPs intended for vascular devices. While kinetic experiments using immersion DMA indicate slight material relaxation and a decrease in the time to recovery, these changes are not found for bulk recovery experiments. The results indicate that a two-year shelf-life for these SMPs is very reasonable, as there is no change in the recovery kinetics, strain recovery, or strain fixity associated with this aging time. Further, a thermal accelerated aging test is presented for more rapid testing of the shape memory behavior of these SMPs and is compared with the real time aging results, indicating that this test is a reasonable indicator of the two-year behavior.